(untitled) (Journal of Hama University, 2025)
The aim of the research is to identify the degree of the university’s application of community partnership from the point of view of the educational qualification diploma students, with a proposed vision for activating it at the university Hama are education and science, and their number is (87) male and female students, and the research sample was limited to (44) of them, There are statistically significant differences about the university’s application of community partnership due to the variable of specialization and in favor of the students of the College of Education.